Repositioning the Independence of the Indonesian Waqf Board in the Development of National Waqf: A Critical Review of Law No. 41 of 2004 Concerning Waqf - Rimanto Rimanto; Sonny Zulhuda; Agus Hermanto (Justicia Islamica, 2021)
Juridically, the laws and regulations have weakened the Indonesian Waqf Board (BWI) in the regulation of waqf so that the set goals of the Indonesian Waqf Board have not been fully achieved, including advancing and developing national waqf. Other institutions' overlapping management and supervision of waqf is suspected of causing BWI’s duties and authorities’ inadequacy. Besides, several crucial problems, including the Indonesian Waqf Board (BWI), have implications for the stagnation of BWI provisions’ implementation. These regulations have not been followed by the Indonesian Muslim community as a whole. Examining why the Indonesian Waqf Board cannot function correctly is interesting. This study’s objective was to find ideal constructions about BWI's position, duties, and authorities in advancing and developing national waqf. This study was a scientific evaluation with its qualitative-descriptive-analytical characteristics. The method used was qualitative analysis, and the results were presented descriptively. The pattern of reconstructing authority of the Indonesian Waqf Board (BWI) was a study of Law Number 41 of 2004 concerning Waqf so that articles were compiled to lead to a genuinely independent, credible, and robust board in the governance of the Republic of Indonesia. Besides, it is necessary to have accreditation for BWI so that its management’s standardization is credible.